2014
DOI: 10.1007/s10461-014-0846-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Compensation Following Male Circumcision: Results from a Two-Year Prospective Cohort Study of Recently Circumcised and Uncircumcised Men in Nyanza Province, Kenya

Abstract: We present the results of the first study of longitudinal change in HIV-associated risk behaviors in men before and after circumcision in the context of a population-level voluntary medical male circumcision (VMMC) program. The behaviors of 1,588 newly circumcised men and 1,598 age-matched uncircumcised controls were assessed at baseline, 6, 12, 18 and 24 months of follow-up. Despite the precipitous decline in perception of high HIV risk among circumcised men (30-14 vs. 24-21 % in controls) and increased sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 48 publications
7
67
0
Order By: Relevance
“…This effect, commonly known as risk compensation, 34 has been raised in response to preventive interventions, such as vaccination against human papilloma virus and pre-exposure prophylaxis for HIV prevention. [35][36][37] However, prescribing naloxone could also represent an opportunity to increase patients' risk perceptions of opioids. Further research is needed to determine whether practice-based naloxone prescribing increases, reduces or has no effect on opioid-related risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This effect, commonly known as risk compensation, 34 has been raised in response to preventive interventions, such as vaccination against human papilloma virus and pre-exposure prophylaxis for HIV prevention. [35][36][37] However, prescribing naloxone could also represent an opportunity to increase patients' risk perceptions of opioids. Further research is needed to determine whether practice-based naloxone prescribing increases, reduces or has no effect on opioid-related risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the association between circumcision status and delayed sexual initiation in Mali and Ethiopia suggests no concerns about risk compensation in a context where it has been feared that young men could undergo penile circumcision as a passport to engage in risky sexual behaviour [6,23,30]. Rwanda, Uganda and Namibia however, present contexts where concerns around risk compensation would be legitimate given the apparent association between penile circumcisions and early sex as revealed by the findings of this study.…”
Section: Discussionmentioning
confidence: 68%
“…In the South African and Uganda trials [9,10], circumcised men engaged in more risky sexual behaviours following circumcision; and their counterparts in Kenyan were more likely to engage in unprotected sex than uncircumcised men [11]. However, studies conducted in Kisumu, Kenya, found no evidence of risk compensation [22][23][24] with male circumcision while another study in Uganda reported a decline in non-marital relations following circumcision [25]. Other studies have suggested scope for the association between male circumcision and risky sexual behaviours [6,26,27], although there are conflicting results among races [25].…”
Section: Risk Compensationmentioning
confidence: 99%
“…According to Westercamp et al (2014), it is very possible that the behavioural changes observed in circumcised men may reflect a form of cognitive dissonance in which the psychological state of conflict between attitudes, beliefs or behaviours result in realignment to decrease discomfort caused by the conflict-in which men re-evaluate their behaviours in light of the personal investment involved in getting circumcised.…”
Section: Discussionmentioning
confidence: 99%